Feasibility Analysis of PT X’s Oil Palm Plantation Investment Using Capital Budgeting and Scenario Analysis - Chintya Christiana; Indah Melati (Publikasi Indonesia, 2026)
Indonesia is the world’s largest producer of crude palm oil (CPO). By 2024, national CPO production and stocks were projected to exceed 57 million tonnes, allocations for exports of 29.5 million tonnes, biodiesel production of 12 million tonnes, and domestic food consumption of 11.1 million tonnes. This study aimed to analyze the investment feasibility of PT X’s 300-hectare oil palm plantation expansion in West Kalimantan using capital budgeting and scenario analysis. A qualitative descriptive single-case study design was employed using primary data obtained from management interviews and field observations, as well as secondary data from PT X’s internal financial model, Bappebti CPO data, Bank Indonesia government securities (Surat Berharga Negara/SBN) yield data, and Damodaran financial data. Eight financial evaluation methods were applied: Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Discounted Payback Period (DPP), Profitability Index (PI), Cost of Debt, Capital Asset Pricing Model (CAPM), and Weighted Average Cost of Capital (WACC). All feasibility indicators demonstrated positive results, with an NPV of IDR 23.978 billion at a 12% discount rate and IDR 20.459 billion based on WACC of 13.16%; an IRR of 26.78%; a PP of 6.95 years; a DPP of 8.46 years; and a PI of 3.33. Scenario analysis across six land-price variations (IDR 15–34 million/hectare) confirmed investment feasibility under all scenarios, with IRR values ranging from 26.78% to 39.56%. The IRR–WACC spread of 13.62 percentage points indicated significant economic value creation, with an estimated Economic Value Added (EVA) of IDR 4.68 billion per year.